Improved antibacterial and cellular response of electrets and piezobioceramics. (September 2021) - Singh, Angaraj; Dubey, Ashutosh Kumar
The bacterial contamination in implants has been recognized as one of the key issues in orthopedics. In this article, a new technique of electrical polarization of various non-piezoelectric and piezoelectric biocompatible ceramics has been explored to develop antibacterial implants. Optimally processed hydroxyapatite (HA), BaTiO3 (BT), CaTiO3 (CT), Na0.5 K0.5 NbO3 (NKN) and their composites have been used as model biomaterials to verify the concept. The phase evolution analyses and microstructural characterizations were performed for sintered samples. The samples were polarized at polarizing voltage and temperature of 20 kV and 500°C, respectively, for 30 min. The hydrophilicity of polarized surfaces was examined using deionized water and culture media. The polarization induced in-vitro antibacterial study was performed for both, gram positive and gram negative bacteria. The viability of Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ) bacteria reduces significantly on the polarized surfaces. In addition, the influence of polarization on antibacterial response has been explored via various mechanisms such as development of reactive oxygen species (ROS), catalase activity and lipoperoxidation. Furthermore, the cellular response of polarized surfaces was also examined using SaOS2 and MG-63 cells. The viability of SaOS2 and MG-63 cells was observed to increase significantly on negatively polarized surfaces. Overall, the surface treatment enhances the antibacterial response of HA, NKN, BT, CT and their composites surfaces with positive influence on cellular response.